Stacking‐Controlled Assembly of Cabbage‐Like Graphene Microsphere for Charge Storage Applications. Issue 35 (2nd August 2018) - Kim, Sun Kyung; Lee, Byeongyong; Ha, Taehyeong; Park, Su‐Ryeon; Chang, Hankwon; Lee, Seung Woo; Jang, Hee Dong
Abstract: Nanostructured graphene electrodes generally have a low density, which can limit the volumetric performance for energy storage devices. The liquid‐phase mild reduction process of graphene oxide sheets is combined with the continuous aerosol densification process to produce high‐density graphene agglomerates in the form of microspheres. The produced graphene assembly shows the cabbage‐like morphology with a high density of 0.75 g cm −3 . In spite of such high density, the cabbage‐like graphene microspheres have narrow‐ranged mesopores and a high surface area. The cabbage‐like graphene microsphere exhibits both high gravimetric and volumetric energy densities due to the optimized microstructure, which shows a high gravimetric capacitance of 177 F g −1 and volumetric capacitance of 117 F cm −3 in supercapacitors. As a cathode for lithium‐ion capacitors, the cabbage‐like graphene delivers a reversible capacity of ≈176 mAh g −1 . The stacking‐control approach provides a new pathway to control the microstructure of the graphene assembly and corresponding charge storage characteristics for energy storage applications. Abstract : The liquid‐phase mild reduction process of graphene oxide sheets is combined with the continuous aerosol densification process to produce high‐density graphene agglomerates in the form of microspheres. The cabbage‐like graphene microsphere exhibits both high gravimetric and volumetric energy densities as for supercapacitors and delivers a high reversible capacity for lithium‐ion capacitors.